ChemInform Abstract: Chromones as a Privileged Scaffold in Drug Discovery: A Review. Issue 27 (8th July 2014) - Keri, Rangappa S.; Budagumpi, Srinivasa; Pai, Ranjith Krishna; Balakrishna, R. Geetha
Abstract Review: 151 refs.